Strategi Think Pair Share Dalam Menumbuhkan Kognitif Peserta Didik - Fadhalliah Khoiriyah (Inspiratif Pendidikan, 2024)
Understanding a strategy is very important in the learning process. In an effective learning process, students make changes in positive terms, especially in the process of thinking. The reality of the problems experienced by teachers is that they minimally apply innovative, creative, effective and fun learning strategies so that in the end students feel bored with the learning applied by the teacher. This study aims to determine the Think Pair Share (TPS) strategy in order to increase students' cognitive abilities to remember and to explain the stages of the TPS strategy in order to increase students' cognitive abilities. This research uses qualitative research with the data collection technique is a library research (library research). Library research is a type of qualitative research which is generally carried out by not going into the field in searching for data sources, so this research is carried out based on written works such as books, literature or journals related to the material. The conclusion of this study is that by implementing the think pair share strategy in learning, it can indirectly increase activeness in thinking and students who play a role in the learning process will lead to increased abilities in both cognitive, affective and psychomotor forms of students.